Corporate liquidity, investment and financial constraints: Implications from a multi-period model - Dasgupta, Sudipto; Sengupta, Kunal (Journal of Financial Intermediation, 2007)
In single period models, financially constrained firms invest more in response to increases in their net worth or interest rate cuts. We examine whether or not these results necessarily hold in a multi-period setting. We present a multi-period version of the Holmstrom and Tirole moral hazard model and show that the probability of investment (or the hurdle rate for investment) in the first period of a two-period model is non-monotonic in the level of liquid balances [Holmstrom, B., Tirole, J., 1997. Financial intermediation, loanable funds, and the real sector. Quart. J. Econ. 112 (3), 663–691. August; Holmstrom, B., Tirole, J., 1998. Private and public supply of liquidity. J. Polit. Economy 106 (1), 1–40. February; Holmstrom, B., Tirole, J., 2000. Liquidity and risk management. J. Money, Credit, Banking 32 (3), 295–319. August]. When a risk-free interest rate is introduced in the model, we show that a lower interest rate (or a downward shift or the yield curve) can lead to less current investment due to the interaction of future financial constraints and discounting of cash flows. Our results have implications for the effect of monetary policy on investment by financially constrained firms. They also address several recent empirical debates, such as the relationship between liquidity and the cash-flow sensitivity of investment, and whether or not accumulation of cash balances by Japanese firms can be consistent with the existence of financial constraints affecting investment.